Pain, fentanyl consumption, and delirium in adolescents after scoliosis surgery: dexmedetomidine vs midazolam. Issue 5 (28th February 2013) - Aydogan, Mustafa S.; Korkmaz, Mehmet F.; Ozgül, Ulkü; Erdogan, Mehmet A.; Yucel, Aytac; Karaman, Abdurrahman; Togal, Turkan; Durmus, Mahmut; Colak, Cemil; Anderson, Brian
Summary Background The study aim was to compare the efficacy of dexmedetomidine vs midazolam for sedation during the early postoperative period in adolescents who underwent scoliosis surgery. Methods We performed a prospective, randomized trial in an intensive care unit (ICU) in a tertiary care center. In this study, 42 patients (American Society of Anesthesiology physical status I and II) who underwent scoliosis surgery were divided into two groups according to sedation protocols: group dexmedetomidine (DEX) (n = 22) and group midazolam (MDZ) (n = 20). Adolescents (12–18 years) requiring mechanical ventilation underwent a continuous infusion of either dexmedetomidine (group DEX; starting dose, 0.4 μg·kg−1·h−1) or midazolam (group MDZ; starting dose, 0.1 mg·kg−1·h−1) with intermittent fentanyl, as needed. The efficacy of sedation was assessed using the Richmond Agitation Sedation Scale (RASS). Quality of pain relief was measured using the Numeric Visual Analog Scale (NVAS). Delirium was determined in patients in the RASS range of −2 to +1 using the Confusion Assessment Method for the ICU (CAM‐ICU). Fentanyl consumption, incidence of delirium, NVAS scores, and hemodynamics were recorded postoperatively at 2, 4, 6, and 24 h in the ICU. Results The NVAS pain scores and fentanyl consumption at all the evaluation time points were significantly higher in group MDZ than those in group DEX (P < 0.05). Further, total fentanyl consumption in group MDZ was significantly higher than that in group DEX (P < 0.05). Delirium was significantly higher in the group MDZ than that in group DEX (31.3% vs 12.5%) when analyzed as the endpoint of CAM‐ICU (P < 0.05). The heart rate was significantly lower in group DEX compared with that in group MDZ at all the evaluation time points (P < 0.05). Conclusion Dexmedetomidine was associated with the decreased postoperative fentanyl consumption, NVAS scores, and a decreased incidence of delirium. These findings may be beneficial for managing sedation protocols in adolescents who have undergone scoliosis surgery.